A systematic narrative review of International Posture: What is known and what still needs to be uncovered. (June 2020) - Botes, Elouise; Gottschling, Juliana; Stadler, Matthias; Greiff, Samuel
Abstract: The field of research investigating motivational variables in learning English as a Foreign Language (EFL) is large and varied. An emerging variable, International Posture, can be summarised as a revised form of Gardner's (1985) construct of integrativeness, updated by Yashima (2002). To further the understanding of International Posture, we conducted a systematic review of the literature. Data from 66 studies were extracted and four themes emerged from the literature, namely, the design/definition of International Posture, the measures used to quantify International Posture, its position in the nomological network of language learning motivation, and its purported malleability. The narrative review discusses each theme with a specific focus on future research. Overall, International Posture was found to be a valid and useful variable for directly explaining the motivation and indirectly explaining the proficiency of the EFL learner, although further research is needed to confirm the underlying design and measurement of the variable.